A paradigm shift towards Social Europe? The proposed Directive on adequate minimum wages in the European Union - Thorsten Schulten (Italian Labour Law e-Journal, 2021)
In autumn 2020, the European Commission published a proposal for a "Directive on adequate minimum wages in the European Union". For the first time in the history of the EU, draft legislation is on the table which explicitly aims not only to significantly increase the level and scope of minimum wages in Europe, but also to strengthen collective bargaining systems. The proposal thus represents a fundamental paradigm shift in European labour policy. Not so long ago, the Commission essentially viewed adequate minimum wages and strong collective bargaining systems as institutional barriers for the functioning of free markets and thereby as having a negative impact on the development of growth and employment. Indeed, in the wake of the last major economic crisis in 2008/2009, the EU exerted considerable influence in many countries towards freezing or even decreasing minimum wages and weakening collective bargaining systems. Now the European Commission’s approach is the exact opposite: by upgrading minimum wages and extending collective bargaining, the main aim is to strengthen the bargaining position of workers. The adoption of the Directive would mark a significant step towards a more “Social Europe”. However, the debate on the Directive is shaped by various political and legal fault lines so that its adoption is still anything but certain.